Cooperative Learning Group for English Teachers: A School-based Teachers' Professional Development - Rahayu, Puji; Astuti, Irma Windy (English Education Department, Universitas Islam Indonesia, 2009)
The process of civil servant teacher's recruitment makes a school to possibly have both, or either, qualified and under qualified English teachers. The former can observe their job as teachers well while the later might not. The case is worse when they are not only incapable of teaching well but also still need help in their English proficiency. Asking them to take an English class is almost impossible. There must be ways of developing then professionalism while they are performing their tasks as teachers.Building a cooperative learning group for English teachers will improve their professionalism, both the qualified and under qualified ones, with its very slogan